The “root” causes behind the anti-inflammatory actions of ginger compounds in immune cells - Pázmándi, Kitti; Szöllősi, Attila Gábor; Fekete, Tünde (Frontiers in Immunology, 2024)
Ginger (Zingiber officinale) is one of the most well-known spices and medicinal plants worldwide that has been used since ancient times to treat a plethora of diseases including cold, gastrointestinal complaints, nausea, and migraine. Beyond that, a growing body of literature demonstrates that ginger exhibits anti-inflammatory, antioxidant, anti-cancer and neuroprotective actions as well. The beneficial effects of ginger can be attributed to the biologically active compounds of its rhizome such as gingerols, shogaols, zingerone and paradols. Among these compounds, gingerols are the most abundant in fresh roots, and shogaols are the major phenolic compounds of dried ginger. Over the last two decades numerous in vitro and in vivo studies demonstrated that the major ginger phenolics are able to influence the function of various immune cells including macrophages, neutrophils, dendritic cells and T cells. Although the mechanism of action of these compounds is not fully elucidated yet, some studies provide a mechanistic insight into their anti-inflammatory effects by showing that ginger constituents are able to target multiple signaling pathways. In the first part of this review, we summarized the current literature about the immunomodulatory actions of the major ginger compounds, and in the second part, we focused on the possible molecular mechanisms that may underlie their anti-inflammatory effects.